Pengembangan Usaha pada Rumah Makan Kemang Jaya menggunakan Bussiness Model Canvasing - Wianda Oktavia; Dewi Fadila; Paisal . (Jurnal Ekonomi dan Bisnis Digital, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are one of the biggest supports for the national economy in Indonesia. MSMEs in Indonesia are also of various types from each region. Kemang Jaya Restaurant Business is one of the MSMEs engaged in the culinary sector located on Jl. R. Suprapto No. 184, Kemang Manis, Ilir Barat Ii 30144 Palembang. The Kemang Jaya Restaurant business has never used any promotional media in marketing. This research was conducted to find out four aspects, namely Production, Finance, Human Resources (Human Resources), and Marketing and producing a digital marketing design in the Kemang Jaya Restaurant business by taking advantage of internet use opportunities in Indonesia. This research uses a qualitative method. The results of this research are in the form of digital marketing designs through social media WhatsApp Business, Instagram and Tiktok. The results of the study explain that the type of content that is most in demand by social media users is the type of content that is most interested in social media users. through video reels. The results of this research are expected to be a reference for business managers of Kemang Jaya Restaurant.